(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The attainment of inter-regional price equilibrium is of immense importance in an economy to achieve the marketing and pricing objectives of a commodity. Since Nigeria has witnessed an established growing demand for rice as propelled by rising per capita consumption, the need for a well integrated rice marketing system arises due to high demand. This study therefore, described growth rate in retail prices, determined long-run and short-run price equilibrium among different pairs of spatially separated markets in Nigeria for imported and local rice varieties. Monthly retail prices of both rice varieties from January 2001 to December 2010 (120 months/state) were obtained for six geo-political zones of Nigeria from the statistical database of National Bureau of Statistics. Three (urban) markets were randomly selected from each zone, making eighteen markets across the six geo-political zones. Analytical techniques used were Augmented Dickey Fuller (ADF) unit root test, Johansen multivariate co-integration technique, Vector Error Correction Modelling (VECM) and Granger causality test. The findings revealed that for the imported rice markets, Ebonyi recorded the highest growth rate in retail prices (70.17%) and (85.52%) in 2004 and 2008, respectively. However, for the local rice markets, Bayelsa recorded the highest growth rate of 86.05% in 2003, followed by Lagos (72.01%) in 2005 and Bauchi (45.85%) in 2007. The results of ADF unit root test revealed that price series variables were non-stationary at levels but became stationary after the first-differencing for imported and local rice varieties at 5% level of significance. Also, about 85.00% of the imported rice markets exhibited long-run price equilibrium while the local rice markets exhibited 71.90% long-run price equilibrium. The imported and local rice markets were well spatially integrated with 83.00% shock in imported rice prices being transmitted to the local rice prices due to policy implications. The VECM results revealed moderate short-run price equilibrium among the imported rice markets while there was weak shortrun price equilibrium in the local rice markets. The results of Pair-wise Granger causality test for imported and local rice market links in the same state showed that ten market links exist between imported rice and local rice markets in bi-directional (two- way) causality. The study showed that price signals were well transmitted across spatially separated markets for local rice varieties, thus indicating integration of rice markets in Nigeria between January 2001 and December 2010.